Analisis Keterampilan Digital Aparatur Sipil Negara dalam Proses Bisnis Era Industri 4.0: Studi Kualitatif pada Institut Pemerintahan Dalam Negeri (IPDN) - Ernawan, Ernawan; Azie Nur Sidik Muchidin; Franciskus Antonius Alijoyo (Universitas Pasundan, 2025)
Fourth Industrial Revolution has brought significant changes to various aspects of life, including the workplace and business processes. This era is characterized by the integration of advanced technologies such as the Internet of Things (IoT), artificial intelligence (AI), big data, and blockchain into daily operations. According to the World Economic Forum (2020), approximately 50% of all jobs worldwide will experience significant changes due to technological advancements. Digital transformation not only affects the private sector but also the public sector, including Civil Servants (ASN) who play a crucial role in public service delivery. This study aims to analyze the digital skills of Civil Servants (ASN) in business processes during the Fourth Industrial Revolution, with a focus on the Institute of Public Administration (IPDN). The study also aims to identify the challenges and barriers faced by ASN in developing digital skills and strategies that can be applied to enhance digital competence. The results show that the digital skills of ASN at IPDN need to be enhanced, particularly in the use of advanced technologies and data analysis. Although most ASN are familiar with using basic hardware and software, there is still a gap in their mastery of more advanced technologies. ASN have a crucial role in business processes during the Fourth Industrial Revolution, particularly in digitalizing public services and making data-driven decisions. However, limitations in digital skills can hinder the efficiency and effectiveness of business processes. The challenges and barriers faced by ASN in developing digital skills include skill gaps, resistance to change, and the availability of digital infrastructure. Strategies for developing digital skills of ASN should focus on competence enhancement through training, the development of a digital work culture, and policy and leadership.